STRATA SOSIAL JAWA NOVEL PARA PRIYAYI: KAJIAN SOSIOLOGI SASTRA - Annissa Bunga Adhyatri; Iis Suminar; Enung Nurhayati (IKIP Siliwangi, 2019)
Javanese culture in the discussion of modern novels today includes people whose cultural uniqueness, behavior, and the principle of life that distinguishes it from other cultures. Umar Kayam in Priyayi clearly described the life of a certain Javanese aristocrat called the priyayi from the last period the Colonial to the Age of Independence. This study tries to uncover the social strata of the priyayi, using the sociological approach of literature. This study describes the social strata of Java that are realized through the behavior of the main characters the novel PP and analyze it. By analyzing the Javanese social strata, it is hoped that an objective picture of Javanese social strata will be obtained the novel PP by Umar Kayam. Sastrodarsono who came from the lower classes in Javanese society was able to achieve aristocratic priyayi status and build his own aristocratic dynasty. He internalized priyayi values and socialized to his family. This novel gives a brief view of the social mobilization of Javanese aristocratic families and the elements that make up the priyayi identity.